Talidomid - nowe znaczenie terapeutyczne teratogennego leku = Thalidomide – new therapeutic value of teratogenic drug - Surowiec, Agnieszka; Wołowiec, Łukasz; Surowiec, Justyna; Wołowiec, Małgorzata; Kochański, Bartosz; Kałużny, Krystian; Plaskiewicz, Anna; Krakowska, Alicja; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Surowiec Agnieszka, Wołowiec Łukasz, Surowiec Justyna, Wołowiec Małgorzata, Kochański Bartosz, Kałużny Krystian, Plaskiewicz Anna, Krakowska Alicja, Zukow Walery. Talidomid - nowe znaczenie terapeutyczne teratogennego leku = Thalidomide – new therapeutic value of teratogenic drug. Journal of Education, Health and Sport. 2015;5(6):341-354. ISSN 2391-8306. DOI 10.5281/zenodo.18712 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A341-354 https://pbn.nauka.gov.pl/works/567418 http://dx.doi.org/10.5281/zenodo.18712 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 16.06.2015. Talidomid - nowe znaczenie terapeutyczne teratogennego leku Thalidomide – new therapeutic value of teratogenic drug Agnieszka Surowiec1, Łukasz Wołowiec1, Justyna Surowiec2, Małgorzata Wołowiec3, Bartosz Kochański4, Krystian Kałużny4, Anna Plaskiewicz4, Alicja Krakowska4, Walery Zukow5 1Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2Studenckie Koło Naukowe anatomii topograficznej człowieka, Katedra anatomii człowieka, Międzynarodowy Uniwersytet Medyczny w Ivano- Frankivsku 3Koło Naukowe Psychologii Zarządzania, Katedra Nauk Społecznych, Katolicki Uniwersytet Lubelski Jana Pawła II 4Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 5Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Szpiczak mnogi (MM) jest drugim co do częstości nowotworem hematologicznym. Interakcje między komórkami szpiczaka i mikrośrodowiska są niezbędne dla przetrwania komórek MM. W szpiczaku mnogim, występują zaburzenia dotyczące komórek plazmatycznych (komórek szpiczaka), gromadzących się w szpiku kostnym wielu kości organizmu. W ciągu ostatniej dekady nastąpił znaczny postęp wiedzy o biologii szpiczaka mnogiego (MM) i jego leczeniu. Mimo tej znacznej poprawy, MM wciąż pozostaje chorobą nieuleczalną i skłania do poszukiwania dodatkowych opcji terapeutycznych. Badania kliniczne nad talidomidem stosowanym zarówno w monoterapii jak i w skojarzeniu z innymi lekami, potwierdziły korzyści zarówno w nawrotowym i opornym na leczenie szpiczaku mnogim. Talidomid daje korzystną odpowiedź u chorych na szpiczaka mnogiego stosowany w monoterapii, a ponadto działa synergistycznie z kortykosteroidami i innymi chemioterapeutykami. Wywoływana przez talidomid neuropatia obwodowa jest zwykle symetryczna i charakteryzuje się bolesnymi parestezjami rąk i stóp z często towarzyszącą utratą czucia w stopach. Badania nad mechanizmami działania talidomidu prowadzi do lepszego zrozumienia celów terapeutycznych na poziomie molekularnym. Abstract Multiple myeloma (MM) is the second most common hematological malignancy. Interactions between myeloma cells and the microenvironment are essential for MM cell survival. In multiple myeloma, abnormal plasma cells (myeloma cells) build up in the bone marrow and form tumors in many bones of the body. Major advances have occurred in our understanding of the biology of multiple myeloma and in its treatment in the past decade. Despite this significant improvement in the overall outcome, multiple myeloma remains incurable in the majority of patients, prompting a continued search for additional therapeutic options. Clinical trials both as a single agent and in combination have confirmed benefit in relapsed and refractory disease. Thalidomide is being investigated currently in a number of clinical trials for cancer. Thalidomide causes responses of myeloma patients as a single agent, and acts synergistically with corticosteroids and chemotherapy. Thalidomide-induced peripheral neuropathy is typically symmetrical, and is characterized by painful paresthesia of the hands and feet, often accompanied by sensory loss in the feet. Research on thalidomide mechanisms of action is leading to a better understanding of molecular targets. Słowa kluczowe: Talidomid, Szpiczak mnogi, MM. Key words: Talidomid, Multiple myeloma, MM.